Fever in the returning traveller: the importance of sensitivity - Philip, K E J (BMJ Case Rep, 2015)
We report the case of a 28-year-old man, presenting with episodes of fever and rigours, having recently returned from Cameroon and Uganda. Initial investigations for malaria were negative, and the patient was sent home without a clear diagnosis. Subsequent review of the blood film revealed the presence of Plasmodium ovale. This case highlights the importance of repeated and careful inspection of blood films, given the relatively low sensitivity of rapid diagnostic tests in P. ovale infection. It also illustrates the importance of the travel history in the diagnosis of malaria.